2012
DOI: 10.4103/0971-7749.104794
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Eustachian tube function in chronic suppurative otitis media (tubotympanic type) with reference to its treatment outcome

Abstract: in perforated tympanic membrane and William's test is an essential tool to assess the ETF in intact tympanic membrane. Our present study is undertaken to assess the ETF in patient with CSOM with reference to its treatment outcome. Based on impedance audiometry fi ndings, patients of tubotympanic disease are categorized as totally impaired, partially impaired, and normal ETF. Patients with normal ETF were taken up for myringoplasty. Patients with totally impaired ETF irrespective of middle ear mucosal status (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 8 publications
3
17
0
Order By: Relevance
“…100% success rate was seen in normal ETF, 98% in partially impaired ETF, and 76% in grossly impaired ETF. 8 Our results also correlates with Cohn et al who assessed ETF by using impedence audiometry (Toynbees test). In their study those with normal ETF, showed a graft uptake of 95%, 75% in partially impaired ETF and 69% graft uptake in totally impaired ETF.…”
Section: Relationship Of Graft Uptake With Respect To Etf Testssupporting
confidence: 90%
“…100% success rate was seen in normal ETF, 98% in partially impaired ETF, and 76% in grossly impaired ETF. 8 Our results also correlates with Cohn et al who assessed ETF by using impedence audiometry (Toynbees test). In their study those with normal ETF, showed a graft uptake of 95%, 75% in partially impaired ETF and 69% graft uptake in totally impaired ETF.…”
Section: Relationship Of Graft Uptake With Respect To Etf Testssupporting
confidence: 90%
“…The results of present study are comparable with Mackinnon (19) who observed 81% success rate in patients with normal ETF and 40% in patients with impaired ETF. Study results were compared with other studies in table No 3 (20)(21)(22)(23)(24). After applying the tests of significance it was found that there is no significant association between Eustachian tube function and successful graft take up (P > 0.05).…”
Section: Role Of Impedance Audiometry In Evaluation Of Eustachian Tubmentioning
confidence: 98%
“…The varying topography of the perforation would thus influence the integrity of the mucociliary system, or also the better or worse condition of the latter would influence the appearance of one type of perforation, or another. [16] Priya et al [7] did ETF by Toynbee test with impedance audiometer in tubotympanic type of chronic otitis media. They found dysfunction in 76% cases (gross dysfunction in 17% cases and partial dysfunction in 59% cases).…”
Section: Discussionmentioning
confidence: 99%
“…[6] It might therefore be possible to predict postoperative results such as hearing improvement and disease recurrence, and to choose optimal operative methods like tympanostomy tube insertion, tympanoplasty, cortical mastoidectomy etc., if ETF can be assessed preoperatively. [7] Assessment of ETF is of paramount importance not only before undertaking any surgery for suppurative otitis media but also in establishing its etiological basis.…”
mentioning
confidence: 99%